Liquid Chromatography-Tandem Mass Spectrometry Analysis Demonstrates a Decrease in Porins and Increase in CMY-2 β-Lactamases in Escherichia coli Exposed to Increasing Concentrations of Meropenem - Foudraine, Dimard E.; Aarents, Camiel N. M.; Wattel, Agnes A.; van Boxtel, Ria; Strepis, Nikolaos; ten Kate, Marian T.; Verbon, Annelies; Luider, Theo M.; Klaassen, Corné H. W.; Hays, John; Dekker, Lennard J. M.; Tommassen, Jan; et al. (Frontiers in Microbiology, 2022)
While Extended-Spectrum β-Lactamases (ESBL) and AmpC β-lactamases barely degrade carbapenem antibiotics, they are able to bind carbapenems and prevent them from interacting with penicillin-binding proteins, thereby inhibiting their activity. Further, it has been shown that Enterobacterales can become resistant to carbapenems when high concentrations of ESBL and AmpC β-lactamases are present in the bacterial cell in combination with a decreased influx of antibiotics (due to a decrease in porins and outer-membrane permeability). In this study, a targeted liquid chromatography-tandem mass spectrometry (LC-MS/MS) assay was developed for the detection of the Escherichia coli porins OmpC and OmpF, its chromosomal AmpC β-lactamase, and the plasmid-mediated CMY-2 β-lactamase. BlaCMY-2-like positive E. coli isolates were cultured in the presence of increasing concentrations of meropenem, and resistant mutants were analyzed using the developed LC-MS/MS assay, Western blotting, and whole genome sequencing. In five strains that became meropenem resistant, a decrease in OmpC and/or OmpF (caused by premature stop codons or gene interruptions) was the first event towards meropenem resistance. In four of these strains, an additional increase in MICs was caused by an increase in CMY-2 production, and in one strain this was most likely caused by an increase in blaCTX-M-15 production. The LC-MS/MS assay developed proved to be suitable for the (semi-)quantitative analysis of CMY-2-like β-lactamases and porins within four hours. Targeted LC-MS/MS could have additional clinical value in the early detection of non-carbapenemase-producing carbapenem-resistant E. coli.